2020
DOI: 10.2196/preprints.18576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surveillance of COVID-19 in the General Population Using an Online Questionnaire: Report From 18,161 Respondents in China (Preprint)

Abstract: BACKGROUND The recent outbreak of the coronavirus disease (COVID-19) has become an international pandemic. So far, little is known about the role of an internet approach in COVID-19 surveillance. OBJECTIVE The aim of this study is to investigate whether an online survey can provide population-level information for observing prevalence trends during the early phase of an outbreak and identifying… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…8 Other studies likewise consistently showed significant sex-specific differences in clinical characteristics and prognosis, with male sex as a risk factor for severe disease and mortality. 16,[19][20][21][22] Potential Causes of Sex and Gender Differences in This striking support for a male bias toward worse clinical outcomes in the COVID-19 pandemic demonstrated by the global epidemiologic data deserves investigation of the mechanisms underlying these sex-and perhaps genderbased differences. There are multiple plausible explanations, including (1) sex-specific biological differences (differences in the immune or inflammatory response, genetic profile, hormone types and levels, and differential expression of angiotensin-converting enzyme 2 [ACE2], the receptor for SARS CoV-2); (2) gender-specific behavioral or lifestyle differences; and/or (3) differences in underlying comorbid conditions.…”
Section: Covid-19 and Sex Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other studies likewise consistently showed significant sex-specific differences in clinical characteristics and prognosis, with male sex as a risk factor for severe disease and mortality. 16,[19][20][21][22] Potential Causes of Sex and Gender Differences in This striking support for a male bias toward worse clinical outcomes in the COVID-19 pandemic demonstrated by the global epidemiologic data deserves investigation of the mechanisms underlying these sex-and perhaps genderbased differences. There are multiple plausible explanations, including (1) sex-specific biological differences (differences in the immune or inflammatory response, genetic profile, hormone types and levels, and differential expression of angiotensin-converting enzyme 2 [ACE2], the receptor for SARS CoV-2); (2) gender-specific behavioral or lifestyle differences; and/or (3) differences in underlying comorbid conditions.…”
Section: Covid-19 and Sex Differencesmentioning
confidence: 99%
“…8 Other studies likewise consistently showed significant sex-specific differences in clinical characteristics and prognosis, with male sex as a risk factor for severe disease and mortality. 16,[19][20][21][22]…”
Section: Covid-19 and Sex Differencesmentioning
confidence: 99%